The TRIUMF-ISAC facility: two decades of discovery with rare isotope beams. (27th July 2016) - Ball, G C; Hackman, G; Krücken, R
Abstract: Since 1999, the TRIUMF-ISAC facility has been providing rare isotope beams for nuclear physics experiments. The three pillars of the program are nuclear structure, nuclear astrophysics, and fundamental symmetries. This article reviews highlights of each of these aspects of the ISAC science program, including tests of the collective behaviors, first explained by Bohr, Mottelson and Rainwater, at the limits of nuclear stability, and future prospects with the ARIEL facility at TRIUMF.